2012
DOI: 10.1137/100815104
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Shape from Shading: Ambiguity Analysis and Numerical Approximations

Abstract: In this paper we study a modern, perspective model for shape from shading and its numerical approximation. We show that a new form of the classic concave/convex ambiguity is still present, although the model has been shown to be well-posed under particular assumptions. This analytical result is confirmed by various numerical tests. Moreover, we present convergence results for two iterative approximation schemes recently introduced in the literature. The first one is based on a finite difference discretization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
0
39
0
1
Order By: Relevance
“…By assuming a Lambertian surface and the illumination given by a point light source located at the optical centre of the camera, they feature many well-posedness properties in contrast to their orthographic counterparts. In particular, the quadratic light fall-off due to inverse square law turned out to be very useful in this context [4,18]. Recently, such perspective SfS models with the light source located at the optical centre of the camera have been extended to non-Lambertian reflectance models [2,24] such as the aforementioned Oren-Nayar model [2].…”
Section: Introductionmentioning
confidence: 99%
“…By assuming a Lambertian surface and the illumination given by a point light source located at the optical centre of the camera, they feature many well-posedness properties in contrast to their orthographic counterparts. In particular, the quadratic light fall-off due to inverse square law turned out to be very useful in this context [4,18]. Recently, such perspective SfS models with the light source located at the optical centre of the camera have been extended to non-Lambertian reflectance models [2,24] such as the aforementioned Oren-Nayar model [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Prados and Faugeras 2 derived a specific pinhole parametrization for the surface in the perspective scenario showing that their particular formulation made the SfS problem well-posed. Following, after few years Breuß et al 7 showed that it was actually not completely well-posed.…”
Section: Introductionmentioning
confidence: 99%
“…While for the Lambertian case Prados and Faugeras [15] were able to show that combining the assumption of a projective camera with a light attenuation term may turn the originally ill-posed SfS problem into a partially well-posed one (cf. [6]), no such thorough analysis has been performed for the advanced Oren-Nayar model so far. Moreover, to the best of our knowledge, there is only one work in the entire literature that presents such an in-depth study for a modern non-Lambertian SfS model: In [5], Breuß and Ju investigate important issues such as critical points and convexity in the context of SfS with the Phong model [25].…”
Section: Introductionmentioning
confidence: 99%